Applications of the dense plasma focus to nuclear fusion and plasma astrophysics - Pouzo, Jorge Osvaldo (2003)
This paper investigates the dense plasma focus (DPF)for applications to nuclear fusion processes in reactors and in astro-physical plasmas. The scaling derived from experiments suggests aDPF of 100 MJ could reach break-even in a reactor and providesparameter space information for astrophysical problems. The costand technological problems associated with this achievement areanalyzed and environmental concerns discussed. The results, as ap-plied to several fields of science and technology and space plasmaphysics, are presented.